2022
DOI: 10.1371/journal.pone.0271329
|View full text |Cite
|
Sign up to set email alerts
|

Tune out pain: Agency and active engagement predict decreases in pain intensity after music listening

Abstract: Music is increasingly being recognised as an adjuvant treatment for pain management. Music can help to decrease the experience of both chronic and experimental pain. Cognitive agency has been identified as a specific mechanism that may mediate the analgesic benefits of music engagement however, it is unclear if this specific mechanism translates to acute pain. Previous attempts to understand the cognitive mechanisms that underpin music analgesia have been predominantly lab-based, limiting the extent to which o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Finally, there was a pronounced effect across all subjects, in which listening to their own self-selected music led to increased connectivity between reward network and auditory regions as compared to other recognizable music within the larger western canon. Agency in music listening is known to be an important factor in health outcomes of music-based interventions (Ruud, 1997; Cassidy & Mcdonald, 2009; Howlin et al, 2022). However, here for the first time, we present direct evidence that agency in song selection leads to increased connectivity of auditory and reward networks.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there was a pronounced effect across all subjects, in which listening to their own self-selected music led to increased connectivity between reward network and auditory regions as compared to other recognizable music within the larger western canon. Agency in music listening is known to be an important factor in health outcomes of music-based interventions (Ruud, 1997; Cassidy & Mcdonald, 2009; Howlin et al, 2022). However, here for the first time, we present direct evidence that agency in song selection leads to increased connectivity of auditory and reward networks.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time people with chronic pain report that they sometimes feel trapped and as if their personal world is getting smaller. Music listening can be used to help patients maintain a sense of their personal identity ( Saarikallio et al, 2020 ) and a sense of agency, when people are encouraged to choose their own music ( Howlin and Rooney, 2021b ; Howlin et al, 2022 ). Additionally, music listening is a relatively easy activity, and perceived as less effortful compared to other types of cognitive tasks, which could be beneficial when patients may have diminished cognitive resources available due to the experience of chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation between music pleasantness and pain reduction in healthy subjects was reported, suggesting the importance of the emotional valence for music-induced pain reduction ( 31 ). However, in another study also using experimental pain, the authors found that emotional responses were not correlated to the analgesic effects, but that perception of control in the selected music during the experiment and the engagement with music in the subject's everyday life were the most important parameters ( 55 ). Interestingly, antagonists drugs of endogenous dopamine and opioids did not reduce the effect of music analgesia ( 56 ).…”
Section: Discussionmentioning
confidence: 99%